2004
DOI: 10.1002/ajim.20044
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of cell and plasma redox state in subjects professionally exposed to chromium

Abstract: This study demonstrated that in humans, an oxidative stress occurs for Cr exposures as low as those considered safe. This oxidative stress appears to be able to affect intracellular and plasmatic antioxidant defense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…Additional adenine attenuated ATP depletion, reduced the percentage of PS-exposing cells, and maintained normal RBCs morphology and volume, thereby suggesting that the intracellular ATP level is important in Cr 6+ -induced eryptosis. According to previous reports, increased ROS may be a major mechanism mediating Cr 6+ -induced injury in RBCs and other karyocytes [14,46,47] and increased ROS levels are closely related to eryptosis [48]. We also found that Cr 6+ exposure significantly increased RBCs ROS levels and PS-exposing cells.…”
Section: Discussionsupporting
confidence: 80%
“…Additional adenine attenuated ATP depletion, reduced the percentage of PS-exposing cells, and maintained normal RBCs morphology and volume, thereby suggesting that the intracellular ATP level is important in Cr 6+ -induced eryptosis. According to previous reports, increased ROS may be a major mechanism mediating Cr 6+ -induced injury in RBCs and other karyocytes [14,46,47] and increased ROS levels are closely related to eryptosis [48]. We also found that Cr 6+ exposure significantly increased RBCs ROS levels and PS-exposing cells.…”
Section: Discussionsupporting
confidence: 80%
“…Any of these species could attack DNA, proteins, and membrane lipids, thereby disrupting cellular integrity and functions [149, 150]. …”
Section: Chromiummentioning
confidence: 99%
“…There are numerous occupational-related exposures each year, which have resulted in an increasing public concern about the potential toxic eVects of Cr at ambient level on human (De Mattia et al 2004). Exposure of Cr can be acute or chronic via inhalation and skin contact.…”
Section: Introductionmentioning
confidence: 99%